26. Implementation of a new optimization algorithm in VMAT for the treatment of prostate cancer. (December 2017) - Birba, I.; Robilliard, M.
Abstract : Introduction: The aim of the current study is to evaluate a new optimization algorithm available since the Eclipse's version 13.6 (Varian): Photon Optimizer version 13 (PO13). The purpose is to obtain a treatment planning protocol for prostate cancer treatments, reproducible which can be delivered by the treatment machine (patient's quality assurance QA) and evaluate the dosimetric gain for patients (better organ at risk protection). Methods: In our department, the medical prescription for the patients treated for a prostate cancer is a 75 Gy dose (2.5 Gy per fraction) on the prostate (PTVPRO) and a 46 Gy dose (2 Gy per fraction) on the right and left iliac lymph nodes. Treatments planning are made of 2 treatment plans: a first treatment plan in integrated boost, delivering a dose of 57.5 Gy on the PTVPRO and of 46 Gy on the PTVGGs in 23 fractions, and the 2nd treatment plan with a dose of 17.5 Gy on the PTVPRO in 7 fractions. Plans are optimized with PO13 and are calculated in the Eclipse's Treatment Planning System (AAA algorithm, Varian) version 13.5 in order to be delivered on a Truebeam (Varian) version 2.5 MR2 in VMAT (arcs of 6 MV, dose rate: 600 UM/min). Several adjustable parameters with PO13 are tested on one patient: Normal Tissue Optimization NTO's influence, calculation resolution during the optimization (1.25 mm, 2.5 mm and 5 mm), one or more arcs, optimization volumes, PTV's priority compared to OAR priority, PTV's priority compared to NTO priority, use of the intermediate dose calculation. The methodology used is to obtain the best PTV's cover, changing a single parameter at each optimization without optimising relatively to the OAR at first. Parameters chosen and fixed, the constraints on the OAR are introduced. These parameters will be tested with several patients (reproducibility). The plan's dosimetric evaluation is realised with the following Dose Volume Histogram (DVH): -  For PTV: D95%, D98%, D2%, Dmin and Confomation Number (CN)1. -  For OAR: bladder and rectum (Dmax, V35Gy, V50Gy), femoral heads (Dmax and Dmean). The monitor units number (MU) per arc is also noted. The dosimetric benefit for the patient will be evaluated in comparison with the real treatment plan calculated with the PRO13 algorithm (Progressive Resolution Optimizer algorithm version 13). The validation of the patient QA of these plans will be realised with the portal imager (Gamma index, PDIP Varian). Results: The protocol will be based on the plan presenting a sufficient coverage for the PTV with the best CN taking into account the DVH values on the OAR. The 57.5 Gy plan chosen is Plan_1 (Table 1) with 2 arcs, a priority of 200 on the PTV for a priority of 500 on the NTO (automatic), a calculation resolution of 2.5 mm, an intermediate dose calculation. Plan_2 with a single arc has D98% and D95% reduced by 1 Gy compared to the other plans and Plan_4 has a CN too weak on the two PTV. Plan_3 with a calculation resolution of 1.25 mm seems the same as Plan_1 but the optimization time is multiplied by 2, a resolution of 2.5 mm is therefore preferred. The first results including the OAR's constraints (priority of 100) shows that there is a significant reduction of DVH values V35Gy and V50Gy between the PRO13 and the new protocol in PO13 (Table 1). Conclusions: This study allowed us to simplify our practices with the use of the NTO as a replacement for optimization volumes (rings). It appears that the treatment plans obtained with PO13 allow a better saving of OAR with an equivalent coverage of PTV.